A high-Q planar multi-resonator for UWB chipless RFID tagging and sensing application - Wan Mohammad, Ghazi; Hossain, A. K. M. Zakir; Ibrahimy, Muhammad Ibn; Azam, S. M. Kayser (IEEE AP/MTT/EMC Joint Chapter of Malaysia, 2022)
This paper involves the design and realization of a new planar microstrip parallel L-shaped multi-resonator (PLMR) for the chipless radio frequency identification (CRFID) that works in ultra-wide band (UWB) frequency region. The proposed PLMR has identifying (IDing) and sensing capabilities to work as a tag-sensor. The PLMR works within 5.36 GHz – 8.63 GHz with a high quality-factor (Q) of 412, a very good spatial density of as low as 3.17 mm2/bit, good spectral density of 4.21 bits/GHz, and a coding capacity of 8 bit with one-bit sensing ability. A coding bit stream of 11111111 also is extracted to show the ability of the proposed design. This will motivate the CRFID designers to design a small and high-capacity tag-sensors for UWB applications.